Strategi Komunikasi Lingkungan Pada Curug Madi Dalam Pelestarian Lingkungan - Tjoagam, Chelshia; Adim, Adrio Kusmareza (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
Natural reserves are areas designated as nature sanctuaries characterized by specific wildlife, plants, or ecosystems that require protection and conservation, with their development occurring naturally. One such area is Curug Madi, which is part of the Natural Reserve and Nature Tourism Park of Kawah Kamojang. The environmental conservation of Curug Madi necessitates the involvement of various stakeholders and the implementation of effective environmental communication strategies. This research aims to analyze and identify the environmental communication strategies employed by the management of Curug Madi in their conservation efforts. The methodology used is descriptive qualitative, with data collected through semi-structured interviews and observations. The findings indicate that the management has undertaken various communication initiatives to raise public awareness about the importance of environmental preservation. Through five stages of the communication planning model including research, planning, implementation, measurement, and reporting the management seeks to address challenges faced in maintaining the ecosystem's sustainability at Curug Madi. The study also reveals that local community involvement is crucial in supporting conservation efforts, despite obstacles such as a lack of awareness regarding environmental issues. These findings underscore the need for effective communication strategies to achieve sustainable environmental preservation goals.